Emerging Clinical Benefits of New‐Generation Fat Emulsions in Preterm Neonates. (27th January 2017) - Guthrie, Gregory; Premkumar, Muralidhar; Burrin, Douglas G.
Abstract : Soybean oil–based intravenous fat emulsions (IVFEs) have been the predominant parenteral nutrition IVFE used in the United States for neonates over the past 45 years. Even though this emulsion has proven useful in supplying infants with energy for growth and essential fatty acids, there have been concerns over its composition in the development of several morbidities, ranging from sepsis to liver disease, bronchopulmonary dysplasia, and impaired neurodevelopment and growth. The exact mechanisms that drive these morbidities in preterm infants are multifactorial, but potential contributors include high ω‐6 (n‐6) fatty acid composition, low docosahexaenoic acid and antioxidant supplementation, and the presence of potentially harmful nonnutritive components (eg, phytosterols). To address these issues, new‐generation IVFEs with various types and amounts of fat have been developed containing greater amounts of the medium‐chain fatty acids, long‐chain polyunsaturated fatty acid, docosahexaenoic acid, lower concentrations of ω‐6 polyunsaturated fatty acids, supplemental vitamin E, and low or negligible amounts of phytosterols. This review examines the clinical outcomes associated with different morbidities of parenteral nutrition in neonates who have received either soybean oil–based or new‐generation IVFEs and addresses whether the proposed benefits of new‐generation IVFEs have improved outcomes in the neonatal population.